2020
DOI: 10.3389/fvets.2020.547181
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Short-Term Antibiotic Withdrawal and Long-Term Judicious Antibiotic Use on Resistance Gene Abundance and Cecal Microbiota Composition on Commercial Broiler Chicken Farms in Québec

Abstract: The ever-increasing problem of antibiotic resistance makes routine use of antibiotics in animal production no longer considered as a reasonable and viable practice. The Chicken Farmers of Canada have developed and are implementing an Antimicrobial Use Reduction Strategy, which has the ultimate goal of eliminating the preventive use of medically important antibiotics in broiler chicken and turkey production. However, very little is known about the real overall impact of an antibiotic use reduction strategy in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…A previous study examining AMR in wild small mammals in a variety of environments in the same study region also found that resistance to tetracyclines (conferred by tetA) was significantly more likely to be identified in generic E. coli from animals trapped on swine farms compared to residential areas [51]. Overall, our findings are consistent with recent mounting evidence that the use of antimicrobials in agriculture is a major driver of AMR in intensive farm environments [52][53][54]. In the future, exploration of enteric bacteria and AMR carried by raccoons in different types of environments, including cities, may contribute valuable information concerning the impact of agricultural and urban environments on the microbiome of these animals.…”
Section: Plos Onesupporting
confidence: 90%
“…A previous study examining AMR in wild small mammals in a variety of environments in the same study region also found that resistance to tetracyclines (conferred by tetA) was significantly more likely to be identified in generic E. coli from animals trapped on swine farms compared to residential areas [51]. Overall, our findings are consistent with recent mounting evidence that the use of antimicrobials in agriculture is a major driver of AMR in intensive farm environments [52][53][54]. In the future, exploration of enteric bacteria and AMR carried by raccoons in different types of environments, including cities, may contribute valuable information concerning the impact of agricultural and urban environments on the microbiome of these animals.…”
Section: Plos Onesupporting
confidence: 90%
“…We found no significant changes in partial PMQR gene abundances at day 14 compared to those at days 7 and 21 ( P > 0.05). This is similar to previous reports showing that the abundance of antibiotic resistance genes is not changed significantly after a period of antibiotic discontinuation ( 55 ). In addition, according to previous reports, the use of antibiotics might cause changes in the abundance of genes conferring resistance to other types of antibiotics ( 56 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, in vivo evaluation of such optimized doses in broiler chickens is still lacking. The impact of other antimicrobials on the residential microbiota in broilers has been investigated ( Xiong et al, 2018 ; Luiken et al, 2019 ; Turcotte et al, 2020 ), showing a range of effects, including reduction of overall diversity of the bacterial communities, microbiome metabolic shifts, increasing gut susceptibility to colonization, and stimulation of the development of AMR. In medical research, there are indications that alternatives to antibiotics, including dietary prebiotics, probiotics, and synbiotics (products that combine the simultaneous and potentially synergistic use of pre- and probiotics) ( Gibson et al, 2004 ; Markowiak and Śliżewska, 2017 ) can reverse the perturbations induced by antimicrobial administration ( Korpela et al, 2018 ; Abd El-Hack et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%